The Erdmannshöhle near Hasel, SW Germany: karst environment and cave evolution - Becker, Arnfried; Piepjohn, Karsten; Schröder-Ritzrau, Andrea (Swiss journal of geosciences, 2020)
The Erdmannshöhle is located at the NE margin of the Dinkelberg plateau in SW Germany. With a length of 2315 m, it is the longest cave in the deep open karst area near the village of Hasel. Three main cave levels developed in moderately SW-dipping, thinly bedded and fractured limestones of the Upper Muschelkalk (Triassic). The youngest cave level containing the cave stream is still active. Eighteen samples for U/Th dating were taken from the oldest and the intermediate cave levels. At the oldest cave level, the ages range from 162 to 110 ka, indicating speleothem growth starting in the middle Beringen Glaciation and terminating at the end of the Eem Interglacial. At the intermediate cave level, the ages range from 100 to 12 ka, i.e. early Birrfeld Glaciation to Younger Dryas Stadial. The age dating shows that speleothem growth did not cease completely during long periods of harsh climate conditions during the Beringen and Birrfeld glaciations and that permafrost terminating speleogenesis and speleothem growth was thus probably established only temporarily over relatively short periods. A conceptual model for the Middle Pleistocene to Holocene development of the Erdmannshöhle is presented within the framework of modern Quaternary lithostratigraphy. This model facilitates a first correlation of the cave evolution with the Middle to Late Pleistocene depositional record in the Möhlinerfeld, which is a key area for modern Quaternary lithostratigraphy in Switzerland and Southern Germany. Thus, speleological and Quaternary research, both based on a regional scale data compilation, complement one another with respect to the timing of events and the landscape evolution during the Quaternary and Late Neogene.
Gesehen am 28.07.2020